A high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y and a preparation method thereof

By adding rare earth element Y to the TiZrNbHfTaW-based refractory high-entropy alloy and optimizing the smelting process, the problems of high brittleness and poor corrosion resistance of refractory high-entropy alloy are solved, and the comprehensive performance of high strength, good plasticity and excellent corrosion resistance are achieved.

CN118621199BActive Publication Date: 2025-04-04HARBIN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410715860.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-04
Publication Date
2025-04-04
Estimated Expiration
2044-06-04

AI Technical Summary

Technical Problem

The refractory high-entropy alloys with existing BCC structures have high brittleness and poor corrosion resistance.

Method used

The rare earth element Y is added to the TiZrNbHfTaW-based refractory high-entropy alloy, and the content of Y is adjusted through a specific smelting process to improve the plastic toughness and corrosion resistance of the alloy.

Benefits of technology

By adding Y elements, the plasticity and corrosion resistance of high-entropy alloys are improved, while maintaining high strength, achieving a balance between strength and plasticity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118621199B_ABST
    Figure CN118621199B_ABST
Patent Text Reader

Abstract

A high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y and a preparation method thereof, which belongs to the field of refractory high-entropy alloy materials. The purpose of the present invention is to solve the problem that the existing refractory high-entropy alloys with BCC structure have high brittleness and poor corrosion resistance. A high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y comprises the following components by weight percentage: Ti: 11.09% to 11.12%, Zr: 21.02% to 21.1%, Nb: 17.18% to 17.30%, Hf: 8.22% to 8.30%, Ta: 25.08% to 25.20%, W: 17.00% to 17.10%, Y: 0.08% to 0.41%. The present invention adds an appropriate amount of W element to the alloy to improve the fracture strain and yield strength; adding the rare earth element Y can improve the plasticity, toughness and corrosion resistance of the alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of refractory high-entropy alloy materials, and specifically relates to a high-strength and high-temperature-resistant TiZrNbHfTaW series refractory high-entropy alloy containing rare earth Y and a preparation method thereof. Background Art

[0002] High entropy alloys, a new type of structural material, have developed rapidly since they were proposed. High entropy alloys are composed of five or more main elements, and the atomic percentage of each main element is between 5% and 35%. The currently developed metal high entropy alloys include lightweight high entropy alloys and refractory high entropy alloys. Lightweight high entropy alloys are alloy systems based on Al and the fourth period elements Fe, Co, Ni, Cr, Cu, Mn and Ti, and refractory high entropy alloys are based on refractory metal elements Mo, Ti, V, Nb, Hf, Ta and W. Usually, the components of high entropy alloys have an equiatomic ratio or an approximately equiatomic ratio to maximize the configuration entropy, which is conducive to the formation of solid solution phases. Compared with ordinary alloys, high entropy alloys are composed of complex arrangements of different multi-component elements and have many advantages and excellent comprehensive properties, such as high strength, high hardness, oxidation resistance and excellent corrosion resistance. They are widely used in many fields such as electrical engineering, electronics, national defense, aerospace, cryogenics and nuclear power generation.

[0003] Heterogeneous alloys composed of soft and hard phases can usually achieve a good combination of strength and ductility. Compared with FCC structured HEAs, BCC structured HEAs have better strength but higher brittleness. HEAs with multiphase structures are expected to achieve a better balance between strength and plasticity. Cu, Cr, Ni, Co, Ti and Al in lightweight HEAs are all corrosion-resistant elements, while refractory HEAs have poorer corrosion resistance. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of high brittleness and poor corrosion resistance of existing BCC structured refractory high entropy alloys, and to provide a high-strength and high-temperature resistant TiZrNbHfTaW series refractory high entropy alloy containing rare earth Y and a preparation method thereof.

[0005] A high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y comprises the following components by weight percentage: Ti: 11.09%-11.12%, Zr: 21.02%-21.1%, Nb: 17.18%-17.30%, Hf: 8.22%-8.30%, Ta: 25.08%-25.20%, W: 17.00%-17.10%, and Y: 0.08%-0.41%.

[0006] A method for preparing a high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y is specifically completed in the following steps:

[0007] 1. Weigh Ti, Zr, Nb, Hf, Ta, W, and Y metal powders according to the following weight percentages: Ti: 11.09% to 11.12%, Zr: 21.02% to 21.1%, Nb: 17.18% to 17.30%, Hf: 8.22% to 8.30%, Ta: 25.08% to 25.20%, W: 17.00% to 17.10%, and Y: 0.08% to 0.41% to obtain a raw material;

[0008] 2. Wash the raw materials with hydrochloric acid, then put them into the vacuum suspension melting furnace and evacuate to 10 -3 , then introduce argon for 60s to make the argon pressure in the smelting furnace 0.08MPa;

[0009] 3. Melting:

[0010] ①. Under the protection of argon atmosphere, first adjust the power of the vacuum suspension melting furnace to 100kW, melt at 100kW for 5min-10min, then adjust to 150kW, melt at 150kW for 5min-10min, then adjust to 200kW, melt at 200kW for 5min-10min, finally adjust to 150kW, melt at 150kW for 10min-15min, and cool down to 100℃-150℃ with the furnace;

[0011] ②, repeat step 3① 4 to 5 times, turn the material up and down between two smeltings, and cast it after smelting to obtain a high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y.

[0012] Principle of the present invention:

[0013] TiZrNbHfTa series high entropy alloys have excellent properties. In the present invention, an appropriate amount of W element is added to the alloy, which is beneficial to increasing the volume between dendrites and refining grains, thereby improving fracture strain and yield strength. The refractory high entropy alloy with a BCC structure has high strength, but the plasticity, toughness and corrosion resistance may not meet expectations. In the present invention, the rare earth element Y is added to the TiZrNbHfTaW series refractory high entropy alloy, which can improve the plasticity, toughness and corrosion resistance of the alloy. The Y content has a significant effect on the microstructure evolution inside the refractory high entropy alloy, thereby improving the plasticity of the high entropy alloy.

[0014] Beneficial effects of the present invention:

[0015] The Y0.2 high entropy alloy prepared by the present invention has a Y content of 0.2 at.%, and the yield strength at room temperature is maintained at 2127 MPa, while the compressive strain is increased from 15.74% when the Y content is 0 at.% to 19.50%, the plasticity is increased by 12.41%, the self-corrosion voltage is -0.40508 V, and the self-corrosion current is 0.115 μA / cm 2 , the corrosion resistance is improved, so that the high entropy alloy material has both high strength and enhanced plasticity and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is the room temperature compression curve of the Y0 high entropy alloy prepared in Example 1;

[0017] Figure 2 is the polarization curve of the Y0 high entropy alloy prepared in Example 1;

[0018] Figure 3 This is a SEM scan of the Y0 high entropy alloy prepared in Example 1;

[0019] Figure 4 is the room temperature compression curve of the Y0.1 high entropy alloy prepared in Example 2;

[0020] Figure 5 is the polarization curve of the Y0.1 high entropy alloy prepared in Example 2;

[0021] Figure 6 The room temperature compression curve of the Y0.2 high entropy alloy prepared in Example 3;

[0022] Figure 7 The polarization curve of the Y0.2 high entropy alloy prepared in Example 3;

[0023] Figure 8 This is a SEM scan of the Y0.2 high entropy alloy prepared in Example 3;

[0024] Fig. 9 is the room temperature compression curve of the Y0.3 high entropy alloy prepared in Example 4;

[0025] Fig.10 is the polarization curve of the Y0.3 high entropy alloy prepared in Example 4;

[0026] Fig.11 is the room temperature compression curve of the Y0.4 high entropy alloy prepared in Example 5;

[0027] Fig.12 is the polarization curve of the Y0.4 high entropy alloy prepared in Example 5;

[0028] Fig.13 The room temperature compression curve of the Y0.5 high entropy alloy prepared in Example 6;

[0029] Fig.14 This is the polarization curve of the Y0.5 high entropy alloy prepared in Example 6. DETAILED DESCRIPTION

[0030] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.

[0031] Specific implementation method 1: This implementation method is a high-strength, high-temperature resistant TiZrNbHfTaW refractory high-entropy alloy containing rare earth Y, which includes the following components by weight percentage: Ti: 11.09%~11.12%, Zr: 21.02%~21.1%, Nb: 17.18%~17.30%, Hf: 8.22%~8.30%, Ta: 25.08%~25.20%, W: 17.00%~17.10%, Y: 0.08%~0.41%.

[0032] Specific embodiment 2: This embodiment differs from the specific embodiment 1 in that the high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y comprises the following components by weight percentage: Ti: 11.12%, Zr: 21.09%, Nb: 17.24%, Hf: 8.25%, Ta: 25.17%, W: 17.05%, Y: 0.08%. The other steps are the same as those of the specific embodiment 1.

[0033] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y comprises the following components by weight percentage: Ti: 11.11%, Zr: 21.07%, Nb: 17.23%, Hf: 8.24%, Ta: 25.14%, W: 17.04%, Y: 0.17%. The other steps are the same as those of specific embodiment 1 or 2.

[0034] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y comprises the following components by weight percentage: Ti: 11.10%, Zr: 21.05%, Nb: 17.21%, Hf: 8.23%, Ta: 25.12%, W: 17.03%, Y: 0.26%. The other steps are the same as those of specific embodiments 1 to 3.

[0035] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y comprises the following components by weight percentage: Ti: 11.10%, Zr: 21.04%, Nb: 17.20%, Hf: 8.23%, Ta: 25.10%, W: 17.01%, Y: 0.32%. The other steps are the same as those of specific embodiments 1 to 4.

[0036] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y comprises the following components by weight percentage: Ti: 11.09%, Zr: 21.02%, Nb: 17.18%, Hf: 8.22%, Ta: 25.08%, W: 17.00%, Y: 0.41%. The other steps are the same as those of specific embodiments 1 to 5.

[0037] Specific embodiment 7: This embodiment is a method for preparing a high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y, which is specifically completed in the following steps:

[0038] 1. Weigh Ti, Zr, Nb, Hf, Ta, W, and Y metal powders according to the following weight percentages: Ti: 11.09% to 11.12%, Zr: 21.02% to 21.1%, Nb: 17.18% to 17.30%, Hf: 8.22% to 8.30%, Ta: 25.08% to 25.20%, W: 17.00% to 17.10%, and Y: 0.08% to 0.41% to obtain a raw material;

[0039] 2. Wash the raw materials with hydrochloric acid, then put them into the vacuum suspension melting furnace and evacuate to 10 -3 , then introduce argon for 60s to make the argon pressure in the smelting furnace 0.08MPa;

[0040] 3. Melting:

[0041] ①. Under the protection of argon atmosphere, first adjust the power of the vacuum suspension melting furnace to 100kW, melt at 100kW for 5min-10min, then adjust to 150kW, melt at 150kW for 5min-10min, then adjust to 200kW, melt at 200kW for 5min-10min, finally adjust to 150kW, melt at 150kW for 10min-15min, and cool down to 100℃-150℃ with the furnace;

[0042] ②, repeat step 3① 4 to 5 times, turn the material up and down between two smeltings, and cast it after smelting to obtain a high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y.

[0043] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the impurity content of a single metal powder in the Ti, Zr, Nb, Hf, Ta, W and Y metal powders weighed in step 1 is less than 0.03%, and the total impurity content of the Ti, Zr, Nb, Hf, Ta, W and Y metal powders is less than 0.1%; the mass fraction of the hydrochloric acid in step 2 is 5% to 20%. The other steps are the same as those in specific embodiments 1 to 7.

[0044] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 3①, under the protection of argon atmosphere, the power of the vacuum suspension melting furnace is first adjusted to 100 kW, and the melting is carried out at 100 kW for 5 min, then adjusted to 150 kW, and the melting is carried out at 150 kW for 5 min, then adjusted to 200 kW, and the melting is carried out at 200 kW for 5 min, and finally adjusted to 150 kW, and the melting is carried out at 150 kW for 15 min, and the temperature is cooled down to 100° C. with the furnace. The other steps are the same as those of specific embodiments 1 to 8.

[0045] Specific implementation method 10: This implementation method is different from specific implementation methods 1 to 9 in that: in step 3 ②, step 3 ① is repeated 5 times. The other steps are the same as those of specific implementation methods 1 to 9.

[0046] The following examples are used to verify the beneficial effects of the present invention:

[0047] Example 1: A method for preparing a Ti25Zr25Nb20Hf5Ta15W10 high entropy alloy is specifically completed by the following steps:

[0048] 1. Weigh Ti, Zr, Nb, Hf, Ta, and W metal powders according to the following weight percentages: Ti: 11.1%, Zr: 21.1%, Nb: 17.2%, Hf: 8.3%, Ta: 25.2%, and W: 17.1% to obtain a raw material;

[0049] 2. Wash the raw materials with hydrochloric acid, then put them into the vacuum suspension melting furnace and evacuate to 10 -3 , then introduce argon for 60s to make the pressure of argon in the smelting furnace 0.08MPa;

[0050] 3. Melting:

[0051] ①. Under the protection of argon atmosphere, first adjust the power of the vacuum suspension melting furnace to 100kW, melt at 100kW for 5min, then adjust to 150kW, melt at 150kW for 5min, then adjust to 200kW, melt at 200kW for 5min, finally adjust to 150kW, melt at 150kW for 15min, and cool down to 100℃ with the furnace;

[0052] ②. Repeat step 3① 5 times. Turn the material upside down between two smeltings. After smelting, pour it to obtain Ti25Zr25Nb20Hf5Ta15W10 high entropy alloy (referred to as Y0 high entropy alloy).

[0053] The room temperature compression curve of the Y0 high entropy alloy prepared in Example 1 is shown in Figure 1 As shown, the relevant performance test data are shown in Table 1; the polarization curve of the Y0 high entropy alloy prepared in Example 1 is shown in Figure 2 As shown, the relevant performance test data are shown in Table 2; the SEM scanning image of the Y0 high entropy alloy prepared in Example 1 is shown in Figure 3 Shown

[0054] Depend on Figure 3 It can be seen that the Y0 high entropy alloy prepared in Example 1 is composed of a white phase, a gray matrix and a black refractory phase, and the white phase is elliptical.

[0055] Embodiment 2: The difference between this embodiment and embodiment 1 is that in step 1, Ti, Zr, Nb, Hf, Ta, W, and Y metal powders are weighed according to the following weight percentages: Ti: 11.12%, Zr: 21.09%, Nb: 17.24%, Hf: 8.25%, Ta: 25.17%, W: 17.05%, and Y: 0.08% to obtain a raw material; the alloy obtained in step 3 is (Ti25Zr25Nb20Hf5Ta15W10) 99.9 Y 0.1 High entropy alloy (denoted as Y0.1 high entropy alloy). Other steps and parameters are the same as those in Example 1.

[0056] The room temperature compression curve of the Y0.1 high entropy alloy prepared in Example 2 is shown in Figure 4 As shown, the relevant performance test data are shown in Table 1; the polarization curve of the Y0.1 high entropy alloy prepared in Example 2 is shown in Figure 5 The relevant performance test data are shown in Table 2.

[0057] Embodiment 3: The difference between this embodiment and embodiment 1 is that in step 1, Ti, Zr, Nb, Hf, Ta, W, and Y metal powders are weighed according to the following weight percentages: Ti: 11.11%, Zr: 21.07%, Nb: 17.23%, Hf: 8.24%, Ta: 25.14%, W: 17.04%, and Y: 0.17% to obtain a raw material; the alloy obtained in step 3 is (Ti25Zr25Nb20Hf5Ta15W10) 99.8 Y 0.2 High entropy alloy (denoted as Y0.2 high entropy alloy). Other steps and parameters are the same as those in Example 1.

[0058] The room temperature compression curve of the Y0.2 high entropy alloy prepared in Example 3 is shown in Figure 6 As shown; the relevant performance test data are shown in Table 1; the polarization curve of the Y0.2 high entropy alloy prepared in Example 3 is shown Figure 7 As shown, the relevant performance test data are shown in Table 2; the SEM scanning image of the Y0.2 high entropy alloy prepared in Example 3 is shown in Figure 8 Shown

[0059] Depend on Figure 8 It can be seen that the Y0.2 high entropy alloy prepared in Example 3 is composed of a white phase and a gray matrix, the black refractory phase is significantly reduced, and the white phase is dendritic.

[0060] Embodiment 4: The difference between this embodiment and embodiment 1 is that in step 1, Ti, Zr, Nb, Hf, Ta, W, and Y metal powders are weighed according to the following weight percentages: Ti: 11.10%, Zr: 21.05%, Nb: 17.21%, Hf: 8.23%, Ta: 25.12%, W: 17.03%, and Y: 0.26% to obtain a raw material; the alloy obtained in step 3 is (Ti25Zr25Nb20Hf5Ta15W10) 99.7 Y 0.3 High entropy alloy (denoted as Y0.3 high entropy alloy). Other steps and parameters are the same as those in Example 1.

[0061] The room temperature compression curve of the Y0.3 high entropy alloy prepared in Example 4 is shown in Fig. 9 As shown; the relevant performance test data are shown in Table 1; the polarization curve of the Y0.3 high entropy alloy prepared in Example 4 is shown Fig.10 The relevant performance test data are shown in Table 2.

[0062] Embodiment 5: The difference between this embodiment and embodiment 1 is that in step 1, Ti, Zr, Nb, Hf, Ta, W, and Y metal powders are weighed according to the following weight percentages: Ti: 11.10%, Zr: 21.04%, Nb: 17.20%, Hf: 8.23%, Ta: 25.10%, W: 17.01%, and Y: 0.32% to obtain a raw material; the alloy obtained in step 3 is (Ti25Zr25Nb20Hf5Ta15W10) 99.6 Y 0.4 High entropy alloy (denoted as Y0.4 high entropy alloy). Other steps and parameters are the same as those in Example 1.

[0063] The room temperature compression curve of the Y0.4 high entropy alloy prepared in Example 5 is shown in Fig.11 As shown; the relevant performance test data are shown in Table 1; the polarization curve of the Y0.4 high entropy alloy prepared in Example 5 is shown Fig.12 The relevant performance test data are shown in Table 2.

[0064] Embodiment 6: The difference between this embodiment and embodiment 1 is that in step 1, Ti, Zr, Nb, Hf, Ta, W, and Y metal powders are weighed according to the following weight percentages: Ti: 11.09%, Zr: 21.02%, Nb: 17.18%, Hf: 8.22%, Ta: 25.08%, W: 17.00%, and Y: 0.41% to obtain a raw material; the alloy obtained in step 3 is (Ti25Zr25Nb20Hf5Ta15W10) 99.5 Y 0.5 High entropy alloy (denoted as Y0.5 high entropy alloy). Other steps and parameters are the same as those in Example 1.

[0065] The room temperature compression curve of the Y0.5 high entropy alloy prepared in Example 6 is shown in Fig.13 As shown, the material related performance test data is shown in Table 1; the polarization curve of the Y0.5 high entropy alloy prepared in Example 6 is shown in Fig.14 The relevant performance test data are shown in Table 2.

[0066] Table 1 Room temperature compressive strain, room temperature compressive strength and hardness of each embodiment

[0067]

[0068]

[0069] Table 2 Self-corrosion voltage and self-corrosion current of each embodiment

[0070] plan Self-corrosion voltage(V) <![CDATA[Self - corrosion current (μA / cm 2 )]]> Example 1 -0.48881 0.794 Example 2 -0.43593 1.8 Example 3 -0.40508 0.115 Example 4 -0.49918 2.42 Example 5 -0.49234 0.311 Example 6 -0.48025 0.127

[0071] From the above examples, it can be concluded that: compared with traditional alloys, the high-strength and high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y prepared by the present invention has high strength, high hardness, high plasticity and excellent high-temperature resistance. The plasticity of the Y0 high-entropy alloy is relatively poor. By regulating the addition amount of the rare earth element Y while maintaining its high yield strength, the plasticity, hardness, corrosion resistance and other indicators of the alloy can be improved. The yield strength of the Y0.2 alloy is 2127MPa, the hardness is 664.01HV, the compressive strain is 19.50%, the self-corrosion voltage is -0.40508mV, and the self-corrosion current is 0.115μA / cm 2 Compared with the Y0 alloy, the plasticity, hardness and corrosion resistance are greatly improved, which is the best comprehensive performance among several groups of embodiments, achieving the expected effect of the present invention.

Claims

1. A high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y, characterized in that The high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y comprises the following components by weight percentage: Ti: 11.09% to 11.12%, Zr: 21.02% to 21.1%, Nb: 17.18% to 17.30%, Hf: 8.22% to 8.30%, Ta: 25.08% to 25.20%, W: 17.00% to 17.10%, Y: 0.08% to 0.41%.

2. The high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y according to claim 1, characterized in that The high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y comprises the following components by weight percentage: Ti: 11.12%, Zr: 21.09%, Nb: 17.24%, Hf: 8.25%, Ta: 25.17%, W: 17.05%, Y: 0.08%.

3. The high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y according to claim 1, characterized in that The high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y comprises the following components by weight percentage: Ti: 11.11%, Zr: 21.07%, Nb: 17.23%, Hf: 8.24%, Ta: 25.14%, W: 17.04%, Y: 0.17%.

4. The high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y according to claim 1, characterized in that The high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y comprises the following components by weight percentage: Ti: 11.10%, Zr: 21.05%, Nb: 17.21%, Hf: 8.23%, Ta: 25.12%, W: 17.03%, Y: 0.26%.

5. The high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y according to claim 1, characterized in that The high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y comprises the following components by weight percentage: Ti: 11.10%, Zr: 21.04%, Nb: 17.20%, Hf: 8.23%, Ta: 25.10%, W: 17.01%, Y: 0.32%.

6. The high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y according to claim 1, characterized in that The high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y comprises the following components by weight percentage: Ti: 11.09%, Zr: 21.02%, Nb: 17.18%, Hf: 8.22%, Ta: 25.08%, W: 17.00%, Y: 0.41%.

7. The method for preparing a high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y as claimed in claim 1, characterized in that The preparation method is specifically completed according to the following steps:

1. Weigh Ti, Zr, Nb, Hf, Ta, W, and Y metal powders according to the following weight percentages: Ti: 11.09% to 11.12%, Zr: 21.02% to 21.1%, Nb: 17.18% to 17.30%, Hf: 8.22% to 8.30%, Ta: 25.08% to 25.20%, W: 17.00% to 17.10%, and Y: 0.08% to 0.41% to obtain a raw material; 2. Wash the raw materials with hydrochloric acid, then put them into the vacuum suspension melting furnace and evacuate to 10 -3 , then introduce argon for 60s to make the argon pressure in the smelting furnace 0.08MPa; 3. Melting: ①. Under the protection of argon atmosphere, first adjust the power of the vacuum suspension melting furnace to 100kW, melt at 100kW for 5min-10min, then adjust to 150kW, melt at 150kW for 5min-10min, then adjust to 200kW, melt at 200kW for 5min-10min, finally adjust to 150kW, melt at 150kW for 10min-15min, and cool down to 100℃-150℃ with the furnace; ②, repeat step 3① 4 to 5 times, turn the material up and down between two smeltings, and cast after smelting to obtain a high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y.

8. The method for preparing a high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y according to claim 7, characterized in that The impurity content of a single metal powder in the Ti, Zr, Nb, Hf, Ta, W and Y metal powders weighed in step one is less than 0.03%, and the total impurity content of the Ti, Zr, Nb, Hf, Ta, W and Y metal powders is less than 0.1%; the mass fraction of the hydrochloric acid described in step two is 5% to 20%.

9. The method for preparing a high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y according to claim 7, characterized in that In step 3①, under the protection of argon atmosphere, first adjust the power of the vacuum suspension melting furnace to 100 kW, melt at 100 kW for 5 min, then adjust to 150 kW, melt at 150 kW for 5 min, then adjust to 200 kW, melt at 200 kW for 5 min, finally adjust to 150 kW, melt at 150 kW for 15 min, and cool down to 100 ° C with the furnace.

10. The method for preparing a high-strength, high-temperature-resistant TiZrNbHfTaW-based refractory high-entropy alloy containing rare earth Y according to claim 7, characterized in that In step 3②, repeat step 3① 5 times.

Citation Information

Patent Citations

  • High-strength plastic self-passivation refractory high-entropy alloy and preparation method thereof

    CN114855048A

  • Refractory high-entropy alloy with high plasticity and high toughness and preparation method thereof

    CN117004863A